2010
DOI: 10.1007/s10535-010-0138-4
|View full text |Cite
|
Sign up to set email alerts
|

Citrate transporters play an important role in regulating aluminum-induced citrate secretion in Glycine max

Abstract: To further understand the process of Al-induced citrate secretion from soybean roots, the effect of protein synthesis inhibitor, anion channel blockers, and citrate carrier inhibitors on Al-induced citrate exudation was investigated in Al-resistant soybean cultivar PI 416937. Citrate exudation from roots increased with the increase of Al concentration from 10 to 50 µM and initiated after 4 h of Al exposure. Protein synthesis inhibitor, cycloheximide (CHM; 25 µM) completely inhibited Al-induced citrate secretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…1 μmolL −1 AgNO 3 or 1 mmolL −1 glycerol was used as aquaporin inhibitors (Kong et al 2007). 10 μmolL −1 anthracene-9-carboxylic acid (9-AC, Aladdin Chemistry, Co. Ltd, China), or 5 μmolL −1 4,4′-diisothiocyanostibene-2,2′-disulfonate (DIDS, Tokyo Chemical Industry, Co. Ltd, Japan), or 5 μmolL −1 5-nitro 2-(3-phenylpropylamine) benzoic acid (NPPB, Tokyo Chemical Industry, Co. Ltd, Japan) was used as anion channel inhibitors (You et al 2010;Matveyeva et al 2003). Maize seedlings were transferred to 400 mL nutrient solution containing 1.0 mgL −1 PFOS or PFOA with metabolic or aquaporin or anion-channel inhibitors.…”
Section: Concentration-dependent Uptake Of Pfosmentioning
confidence: 99%
“…1 μmolL −1 AgNO 3 or 1 mmolL −1 glycerol was used as aquaporin inhibitors (Kong et al 2007). 10 μmolL −1 anthracene-9-carboxylic acid (9-AC, Aladdin Chemistry, Co. Ltd, China), or 5 μmolL −1 4,4′-diisothiocyanostibene-2,2′-disulfonate (DIDS, Tokyo Chemical Industry, Co. Ltd, Japan), or 5 μmolL −1 5-nitro 2-(3-phenylpropylamine) benzoic acid (NPPB, Tokyo Chemical Industry, Co. Ltd, Japan) was used as anion channel inhibitors (You et al 2010;Matveyeva et al 2003). Maize seedlings were transferred to 400 mL nutrient solution containing 1.0 mgL −1 PFOS or PFOA with metabolic or aquaporin or anion-channel inhibitors.…”
Section: Concentration-dependent Uptake Of Pfosmentioning
confidence: 99%
“…As early as 1995, Ryan et al observed that inhibitors of anion channels inhibited the Al-activated secretion of malate from wheat roots, providing evidence that Al might activate malate secretion via a channel in the PM in the apical cells of Al-tolerant wheat cells [37]. Increasing evidence shows that the influence of anion channel inhibitors on the Al-activated secretion of OA anions depends on the species of OA anions secreted, plant species, inhibitor concentration, and species (see [13, 30, 37, 62], Table 1). Li et al observed that two citrate carrier inhibitors (pyridoxal 5′-phosphate (PP) and phenylisothiocyanate (PITC)) effectively inhibited citrate secretion, meaning that the Al-activated citrate from rye roots is mediated by citrate carrier [21].…”
Section: Aluminium-induced Secretion Of Organic Acid Anions From Rmentioning
confidence: 99%